Pengembangan Perangkat Pembelajaran dengan Metode Walking Gallery untuk Meningkatkan Kompetensi Mahasiswa Calon Guru - Syamsidah Syamsidah; Ratnawati Ratnawati (Seminar Nasional LP2M UNM, 2019)
This is research and development that aims to find out the stages of developing the learning tools of the Walking Gallery method and to understand how this learning model can improve student competency validly, effectively, and practically. Research and development procedure was conducted using the 4 D model of the Thiagarajan model, Semmel and Semmel using four stages: the defining stage, the design stage, the development stage and the disseminate stage. The research subjects were Bachelor's degree students of the Department of Family Welfare Education who took part in Family Sociology lectures in the odd semester of the Academic Year 2017/2018. The research trial subjects were 25 students. This research data was processed and analyzed descriptively including data on the results of validation/review, learning management, student activities, data analysis on the results of mastery tests on family sociology concepts, implementation of lesson plans and questionnaire responses of students and lecturers on learning tools. Data processing and analysis were done with descriptive analysis. The results showed that the application of the Walking Gallery (WK) learning model was effective in increasing student competency. This can be seen from two aspects, namely the learning implementation which was observed by three observers and the results of the student creativity questionnaire assessment. The results showed that the implementation of the learning process using the Walking Gallery from the user (lecturer) side indicated that 90.91% was carried out very well while from the student side revealed that 86.11% implemented well. Moreover, based on the results of the student creativity questionnaire, it was found that the students were pleased with the effectiveness of the Walking Gallery method. It can be concluded that the student competencies categorized as good is 88.53% (high). Furthermore, it was found valid, effective, and practical learning tool products that can improve student competencies. Moreover, the learning tool was well appreciated by the lecturers of Family Sociology Courses. Learning tool products are lesson plans (RPP-WK), and textbooks for students majoring in Family Welfare Education.